Cardiotocography and Clinical Risk Factors in Early Term Labor: A Retrospective Cohort Study Using Computerized Analysis With Oxford System - Lovers, Aimée A. K.; Ugwumadu, Austin; Georgieva, Antoniya (Frontiers in Pediatrics, 2022)
Objective: The role of Cardiotocography (CTG) in fetal risk assessment around the beginning of term labour is controversial. We used routinely collected clinical data in a large tertiary hospital to investigate whether infants with ‘severe compromise’ at birth exhibited fetal heart rate abnormalities in their first-hour CTGs and/or other clinical risks, recorded as per routine care. Materials & methods: Retrospective data from 27,927 parturitions (single UK tertiary site, 2001–2010) were analysed. Cases were included if the pregnancy was singleton, ≥ 36 weeks’ gestation, cephalic presentation, and if they had routine intrapartum CTG as per clinical care. Cases with congenital abnormalities, planned caesarean section (CS), or CS for reasons other than ‘presumed fetal compromise’ were excluded. We analysed first-hour intrapartum CTG recordings, using intrapartum Oxford System (OxSys) computer-based algorithms. To reflect the effect of routine clinical care, the data was stratified into three exclusive groups: infants delivered by CS for ‘presumed fetal compromise’ within two hours of starting the CTG (Emergency CS, n=113); between two and five hours of starting the CTG (Urgent CS, n=203); and the rest of deliveries (Others, n=27,611). First-hour CTG and clinical characteristics were compared between the groups, sub-divided to those with and without severe compromise: a composite outcome of stillbirth, neonatal death, neonatal seizures, encephalopathy, resuscitation followed by ≥48hrs in neonatal intensive care unit. Two-sample t-test, 2 test and Fisher’s exact test were used for analysis. Results: Compared to babies without severe compromise, those with compromise had significantly higher proportion of cases with baseline fetal heart rate ≥150bpm; nonreactive trace; reduced long-term and short-term variability; decelerative capacity; and no accelerations in the first-hour CTG across all groups. Prolonged decelerations (≥3min) were also more common. Thick meconium and small for gestational age were consistently more common in compromised infants across all groups. There was more often thick meconium, maternal fever ≥38C, sentinel events, and other clinical risk factors in the Emergency CS and Urgent CS compared to the Others group. Conclusion: A proportion of infants born with severe compromise had significantly different first-hour CTG features and clinical risk factors.